Delegation with incomplete and renegotiable contracts - Emanuele Gerratana; Levent Koçkesen (Koç University-TÜSİAD Economic Research Forum (ERF), 2008)
It is well known that delegating the play of a game to an agent via incentive contracts may serve as a commitment device and hence provide a strategic advantage. Previous literature has shown that any Nash equilibrium outcome of an extensive-form principals-only game can be supported as a sequential equilibrium outcome of the induced delegation game when contracts are unobservable and non-renegotiable. In this paper we characterize equilibrium outcomes of delegation games with unobservable and incomplete contracts with and without renegotiation opportunities under the assumption that the principal cannot observe every history in the game when played by her agent. We show that incompleteness of the contracts restricts the set of outcomes to a subset of Nash equilibrium outcomes and renegotiation imposes further constraints. Yet, there is a large class of games in which non-subgame perfect equilibrium outcomes of the principals-only game can be supported even with renegotiable contracts, and hence delegation still has a bite.
Keywords: C72; C78; D86; L13; 330; Strategic Delegation; Incomplete Contracts; Renegotiation